OFDM-CDMA with peak power reduction based on the spreading sequences - Ochiai, H.; Imai, H. (1998 IEEE International Conference on Communications, 1998)
We discuss the construction method of orthogonal sequences for downlink OFDM-CDMA, in terms of the peak to average power ratio (PAPR) of the transmitted signals. The PAPR property is studied based on two orthogonal sets of sequences: Walsh-Hadamard and complementary sequences. It is shown that for relatively few active users, Walsh-Hadamard sequences tend to have very large PAPR, while the PAPR of complementary sequences remains stable near its theoretical value. A simple but effective peak reduction scheme is also proposed for OFDM-CDMA.